Παλαιότεροι πεζογράφοι : Α.Ρ.Ραγκαβής, Δ. Βικέλας, Γ. Βιζυηνός, Κ. Παλαμάς, Γ. Βλαχογιάννης - Σαχίνης, Απόστολος, 1920- (Εστία, 1973)
Α.Ρ.Ραγκαβής -- Δ. Βικέλας -- Γ. Βιζυηνός -- Κ. Παλαμάς -- Γ. Βλαχογίαννης